Pemahaman Literasi Politik Pemilih Pemula dalam Upaya Pencegahan Informasi Hoax Pemilu 2024 - Akhyar Anshori; Rudianto Rudianto; Jehan Ridho Izharsyah (UMSU, 2023)
Beginner voters are part of the community who in their daily lives are inseparable from the use of gadgets or cell phones. The use of gadgets in the context of seeking information, especially political information, must be accompanied by the ability to digest any information obtained so that wrong information can be avoided. Through political literacy, an understanding of receiving political information obtained by first-time voters will be able to have a significant impact on the attitudes of first-time voters toward their political choices in the 2024 election. The purpose of this research is to determine the level of political understanding of first-time voters in Medan City through political literacy in dealing with the dissemination of hoax information on the 2024 election. This research was conducted using a quantitative approach involving 400 first-time voters. Data collection techniques were carried out using a questionnaire tool with data analysis carried out through single table analysis, simple linear regression, and Pearson correlation test. The results of the study found that the t value obtained through count was 7.118 ttable 1.9659 which means that there is an influence between political literacy variables on preventing the spread of hoax information on the 2024 election with a degree value of 0.336 units or 33.6% which is included in the weak category.